Seismic Shot Point Navigation Data supporting Multi-channel Seismic study of the Blake Ridge, offshore eastern North America, acquired during R/V Maurice Ewing expedition EW0008 (2000) ... - Holbrook, W. (Interdisciplinary Earth Data Alliance (IEDA), 2011)
This data set was acquired with the LDEO Multi-Channel Seismic system of the R/V Maurice Ewing during expedition EW0008 conducted in 2000 (Chief Scientist: Dr. W. Steven Holbrook; Investigator: Dr. W. Steven Holbrook). These data files are of ASCII format and include Seismic Shot Point Navigation data that was processed after collection. Data were acquired as part of the project: Three-Dimensional Structure and Physical Properties of a Methane Hydrate Deposit and Methane Gas Reservoir, Blake Ridge, and funding was provided by NSF grant: OCE99-10966. ...